Quantum Transport Through a ``Charge" Kondo Circuit: Effects of Weak Repulsive Interaction in Luttinger Liquid - Nguyen, Thanh Thi Kim; Kiselev, Mikhail N. (Communications in Physics, 2020)
We investigate theoretically quantum transport through the ``charge" Kondo circuit consisting of the quantum dot (QD) coupled weakly to an electrode at temperature \(T+Δ T\) and connected strongly to another electrode at the reference temperature \(T\) by a single-mode quantum point contact (QPC). To account for the effects of Coulomb interaction in the QD-QPC setup operating in the integer quantum Hall regime we describe the edge current in the quantum circuit by Luttinger model characterized by the Luttinger parameter \(g\). It is shown that the temperature dependence of both electric conductance \(G\propto T^{2/g}\) and thermoelectric coefficient \(G_T\propto T^{1+2/g}\) detours from the Fermi-liquid (FL) theory predictions. The behaviour of the thermoelectric power \(S=G_T/G\propto T\) in a regime of a single-channel Kondo effect is, by contrast, consistent with the FL paradigm. We demonstrate that the interplay between the mesoscopic Coulomb blockade in QD and weak repulsive interaction in the Luttinger Liquid \(g=1-α\) \((α \ll 1)\) results in the enhancement of the thermopower. This enhancement is attributed to suppression of the Kondo correlations in the ``charge" circuit by the destructive quantum interference effects.